Effect of Ethyl Acetate Extract of Malacca Leaf (Phyllanthus emblica) on the Growth of Plasmodium falciparum in Vitro - Sir, Habibah Annum; Asmilia, Nuzul; Armansyah TR, T. (Universitas Syiah Kuala, 2024)
This study aimed to determine the antiplasmodium activity of ethyl acetate extract of malacca leaf (Phyllanthus emblica L.) on Plasmodium falciparum in vitro. In this study, five treatment groups with extract dosage of 100, 75, 50, 25, and 5 g / ml were used. For positive control, antimalarial drug artesdiaquine was given. Plasmodium culture used the candle-jar method and the antiplasmodium activity test was carried out by microculture method in vitro. This research used a complete randomized design (RAL), data was analyzed using analysis of variance (ANOVA) and continued with Duncan's tests. The inhibition concentration (IC50) of malacca leaf extract was analyzed using PROBIT SPSS. Antiplasmodium activity was expressed by IC50 value which is the ability to inhibit 50% of Plasmodium growth. The results showed that the IC50 value of the extract was 17,849 g/ml. It can be concluded that the ethyl acetate extract of malacca leaf had good activity as antiplasmodium and the best concentration was 25 g / ml.